Ultrasensitive Detection of Clostridioides difficile Toxins in Stool by Use of Single-Molecule Counting Technology: Comparison with Detection of Free Toxin by Cell Culture Cytotoxicity Neutralization Assay - Hansen, Glen; Young, Stephen; Wu, Alan H. B.; Herding, Emily; Nordberg, Vickie; Mills, Ray; Griego-Fullbright, Christen; Wagner, Aaron; Ong, Chui Mei; Lewis, Shawna; Yoon, Joseph; Estis, Joel; et al. (Journal of clinical microbiology, 2019)
Laboratory tests for Clostridioides difficile infection (CDI) rely on the detection of free toxin or molecular detection of toxin genes. The Singulex Clarity C. diff toxins A/B assay is a rapid, automated, and ultrasensitive assay that detects C. difficile toxins A and B in stool. We compared CDI assays across two prospective multicenter studies to set a cutoff for the Clarity assay and to independently validate the performance compared with that of a cell culture cytotoxicity neutralization assay (CCCNA). Laboratory tests for Clostridioides difficile infection (CDI) rely on the detection of free toxin or molecular detection of toxin genes. The Singulex Clarity C. diff toxins A/B assay is a rapid, automated, and ultrasensitive assay that detects C. difficile toxins A and B in stool. We compared CDI assays across two prospective multicenter studies to set a cutoff for the Clarity assay and to independently validate the performance compared with that of a cell culture cytotoxicity neutralization assay (CCCNA). The cutoff was set by two sites testing fresh samples from 897 subjects with suspected CDI and then validated at four sites testing fresh samples from 1,005 subjects with suspected CDI. CCCNA testing was performed at a centralized laboratory. Samples with discrepant results between the Clarity assay and CCCNA were retested with CCCNA when the Clarity result agreed with that of at least one comparator method; toxin enzyme immunoassays (EIA), glutamate dehydrogenase (GDH) detection, and PCR were performed on all samples. The cutoff for the Clarity assay was set at 12.0 pg/ml. Compared to results with CCCNA, the Clarity assay initially had 85.2% positive agreement and 92.4% negative agreement. However, when samples with discrepant results between the Clarity assay and CCCNA in the validation study were retested by CCCNA, 13/17 (76.5%) Clarity-negative but CCCNA-positive samples (Clarity + /CCCNA − ) became CCCNA − , and 5/26 (19.2%) Clarity + /CCCNA − samples became CCCNA + , resulting in a 96.3% positive agreement and 93.0% negative agreement between Clarity and CCCNA results. The toxin EIA had 59.8% positive agreement with CCCNA. The Clarity assay was the most sensitive free-toxin immunoassay, capable of providing CDI diagnosis in a single-step solution. A different CCCNA result was reported for 42% of retested samples, increasing the positive agreement between Clarity and CCCNA from 85.2% to 96.3% and indicating the challenges of comparing free-toxin results to CCCNA results as a reference standard.